A novel rugby team player selection method integrating the TOPSIS and IPA methods - Wen, T.; Chang, K.; Lai, H.; Liu, Y.; Wang, J. (International Journal of Sport Psychology, 2021)
The selection of rugby players for any match will directly affect the team performance, and the final outcome of the match. Rugby team player selection involves many individual ability and technical performance criteria, making it a multiple criteria decision-making (MCDM) problem. Traditionally, a simple additive weighting method is used to select suitable team players. However, the traditional simple additive weighting method is only capable of unilaterally handling either individual ability criteria or technical performance criteria. In order to effectively solve the above issues, this study combines the order preference by similarity to ideal solution (TOPSIS) method and the importance-performance analysis (IPA) method for rugby team player selection. For numerical verification, this study applies the selection of Taiwanese Army rugby team players as an example to verify the effectiveness of the proposed novel rugby team player selection method. Simulation results show that the proposed method provides a more accurate and reasonable selection mechanism for selecting the best rugby team for a given match than the traditional simple additive weighting and TOPSIS methods. Moreover, the assessment results achieved using the proposed method can provide a reference for future training resource allocation.